Hand care in epidermolysis bullosa. - Santos Ferreira Lima, R.; Najjar Prado de Oliveira, Z.; Leomil de Paula, E.J. (European Journal of Pediatric Dermatology, 2011)
Inherited Epidermolysis Bullosa (EB) is a rare disease characterized by blisters on skin and mucosa after traumas. Milder skin alterations usually are related with EB simplex whereas scarring leading to deformities and extracutaneus complications are more common in dystrophic EB, specially in the recessive subtype. Hand deformities are often found in the latter patients and treatment is important in order to keep independence of daily activities. This article shows the experience of caring EB patient with hand deformities in Hospital das Clínicas in Sao Paulo, Brazil, on a mutual work between both Orthopedic and Dermatology Departments. We revised medical records of 59 patients with EB and hand deformities. All patients were encouraged to use special gloves and orthopedics devices, 25 patients underwent surgery procedures and half of them for more than one time. Hand surgery is an option for the treatment of hand deformities but there is a high rate of new operation.